Enhanced electrochemical supercapacitor performance with a three-dimensional porous boron-doped diamond film. (19th November 2019) - Wang, Xue; He, Yapeng; Guo, Zhongcheng; Huang, Hui; Zhang, Panpan; Lin, Haibo
Abstract : A three-dimensional porous boron-doped diamond film is developed to enhance the electrochemical performance of supercapacitors in a wide potential window. Abstract : Uniform three-dimensional porous boron-doped diamond (P-BDD) film is deposited on a titanium substrate through chemical vapor deposition and employed as an efficient potential electrode for electrochemical double-layer supercapacitors. The electrochemical responses of the BDD electrodes were evaluated by cyclic voltammetry and galvanostatic charge/discharge techniques. The P-BDD film delivers a specific capacitance of 6.02 mF cm −2 under a scan rate of 10 mV s −1, 12.4 times that of a flat BDD film in 0.1 M H2 SO4 electrolyte in a three-electrode configuration. Furthermore, the operating voltage window of a symmetric device containing two pieces of P-BDD electrode could be expanded to 2.0 V and light a yellow light-emitting diode, where the single device presented an admirable energy density of 1.45 μW h cm −2 and power density of 0.5 mW cm −2 . Moreover, the P-BDD film exhibits favorable self-discharge behavior, with a low leakage current as small as 14.9 μA, and presents remarkable cycling stability, with a capacitance retention of 91.6% after 10 000 continuous cycles. The enhanced electrochemical performance can be attributed to the synergistic effect between the BDD film itself, which possesses excellent physical–chemical features, and the three-dimensional porous structure; this corroborates the potential of the P-BDD film as a candidate for future supercapacitor applications.